Flapless Guided Implant Surgeries Compared with Conventional Surgeries Performed by Nonexperienced Individuals: Randomized and Controlled Split-Mouth Clinical Trial - Frizzera, Fausto; Calazans, Nicolas Nicchio Nicolini [UNESP]; Pascoal, Cristiano Hooper; Martins, Menara Elen; Mendonça, Gustavo (Quintessence Publishing, 2021)
Purpose: The study aimed to evaluate the outcomes of flapless guided surgery related to surgery, patient, operator, assistant, and advisor, comparing it with conventional surgery performed by undergraduate students who had never placed implants in patients. Materials and Methods: A randomized controlled split-mouth clinical trial was carried out. Ten patients with bilateral mandibular posterior tooth loss received an implant on each side with conventional flap surgery or flapless guided surgery that was performed by undergraduate students. Surgery time, pain, patient satisfaction, quantity of consumed medications, time of procedure, ease of procedure, anxiety, and stress were assessed. Results: Conventional surgery showed statistically significantly inferior results compared with flapless guided surgery in terms of procedure time (56 minutes, 36 seconds ± 8 minutes, 38 seconds vs 30 minutes, 1 second ± 6 minutes, 2 seconds), consumption of analgesic medications (49 tablets vs 15 tablets), intraoperative (1.75 ± 1.56 vs 0.65 ± 0.64) and postoperative pain (4.62 ± 2.17 vs 1.17 ± 0.72), and operator anxiety (4.76 ± 1.66 vs 3.47 ± 1.50), respectively. Conclusion: Flapless guided implant surgeries performed by individuals with no previous clinical experience showed reduced surgery time and delivered better patient-reported outcomes both in the intraoperative and postoperative periods; reduced medication consumption; and showed better results in the operator and assistant perspectives
Keywords: 3D; computer-guided surgery; dental implant; flapless procedure; surgical guide